Patristiek en die studie van die Nuwe Testament - Stander, Hennie (Hervormde teologiese studies, 1986)
Patristics and the study of the New Testament This article consists of two main parts. In the first part the importance of the study of Patristics is discussed. The author underscores Outler's logion that 'by itself, the New Testament is not a field of inquiry'. The heading of the second part is Instrumenta Studiorum. In this section the author gives a survey of primary and secondary works on Patristics in order to make this field more accessible to scholars.